If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9x+15=3x+39
We move all terms to the left:
9x+15-(3x+39)=0
We get rid of parentheses
9x-3x-39+15=0
We add all the numbers together, and all the variables
6x-24=0
We move all terms containing x to the left, all other terms to the right
6x=24
x=24/6
x=4
| 5d+4d-2d=7 | | 3.3x+5.7=7.9x+1.1 | | -2x+4+4x/5=12 | | 10-j=15 | | 11-2u=-7 | | -10x-10=-10x-10−10x−10=−10x−10 | | 218=78-w | | 7m2=35 | | 9x+8=11x−6 | | 9x=15x+16 | | 3+1/2x=3/4x-5 | | -2+h=-22 | | 5x-(3x-6)=-10 | | 10^(3x-2)=5 | | d-4=19;d=1 | | t-9=28 | | 1.5(4.5+9h)= | | 4p+3=-5p+21 | | 4z2−8z+5= 22 | | -3(x-1)+x=27 | | 9(q−86)=45 | | 3x=14.5/8 | | t+9=28 | | -4x+5=2x-3 | | 145-v=260 | | 30-2c=16 | | 3y+4y+1y+2y=10 | | 4x+6/2=10 | | -1/2a-4=3-1/4a | | 96m-1=3 | | 4+x=46;x=32 | | 9a+5(3-a)=11* |